Pengaruh Pendekatan Tri-N dan Media Interaktif Berbasis Platform Digital Paint 3D Terhadap Hasil Belajar Bangun Ruang di Sekolah Dasar - Harita Nuzul Apriyani; Zainnur Wijayanto; Insanul Qisti Bariyyah (Didaktika Dwija Indria, 2025)
This study aims to analyze the effect of Tri-N approach and interactive media based on Paint 3D digital platform on learning outcomes of building space in elementary school. The method used was pre-experimental design with one group pretest-posttest design, involving one group of grade VI elementary school students who were given treatment. Measurements were taken before and after treatment. Data analysis techniques using Pearson Product Moment correlation and comparative analysis with normalized gain (N-Gain). The results showed a significant increase in student learning outcomes after the application of the Tri-N approach based on Paint 3D digital media. The average pretest score increased from 63.65 to 86.53 in the posttest. The correlation test showed a significance value of 0.007, while the t-test obtained a significance value of 0.001, which indicated a significant difference between the pretest and posttest results. The N-Gain value was in the medium category with a score of 0.6301. These findings indicate that the use of the Tri-N approach and Paint 3D media is effective in improving students' understanding of the material.